Care Coordination of Multimorbidity: A Scoping Study. Issue 1 (2015) - Doessing, Anne; Burau, Viola
Background: A key challenge in healthcare systems worldwide is the large number of patients who suffer from multimorbidity; despite this, most systems are organized within a single-disease framework. Objective: The present study addresses two issues: the characteristics and preconditions of care coordination for patients with multimorbidity; and the factors that promote or inhibit care coordination at the levels of provider organizations and healthcare professionals. Design: The analysis is based on a scoping study, which combines a systematic literature search with a qualitative thematic analysis. The search was conducted in November 2013 and included the PubMed, CINAHL, and Web of Science databases, as well as the Cochrane Library, websites of relevant organizations and a hand-search of reference lists. The analysis included studies with a wide range of designs, from industrialized countries, in English, German and the Scandinavian languages, which focused on both multimorbidity/comorbidity and coordination of integrated care. Results: The analysis included 47 of the 226 identified studies. The central theme emerging was complexity. This related to both specific medical conditions of patients with multimorbidity (case complexity) and the organization of care delivery at the levels of provider organizations and healthcare professionals (care complexity). Conclusions: In terms of how to approach care coordination, one approach is to reduce complexity and the other is to embrace complexity. Either way, future research must take a more explicit stance on complexity and also gain a better understanding of the role of professionals as a prerequisite for the development of new care coordination interventions.